2015
DOI: 10.1111/padm.12188
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emotion in Enabling and Conditioning Public Deliberation Outcomes: A Sociological Investigation

Abstract: Citizen participation in deliberation activities within public health systems is increasingly seen as essential in achieving more patient‐centred, equitable and democratic care. However, recent studies show that patients' lived, affective experience of illness and care remains poorly understood within deliberative fora. In response, this article argues that emotion is central in mediating deliberation, and in conditioning deliberative outcomes. To understand how this occurs, we use a sociologically informed no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
(43 reference statements)
1
17
0
1
Order By: Relevance
“…We advocate that aspiring and striving to meet the principles outlined in our literature review is essential to achieving impact, and also essential to ensuring that the involvement experience is positive and sustainable. Our evaluation highlighted 'fun' and enjoyment, emotion and sharing lived experiences as essential to making involvement a meaningful and worthwhile activity for public advisers, and while this repeats findings from other evaluations, these elements are not present in the standard list of principles [29,31,32].…”
Section: Discussionsupporting
confidence: 76%
“…We advocate that aspiring and striving to meet the principles outlined in our literature review is essential to achieving impact, and also essential to ensuring that the involvement experience is positive and sustainable. Our evaluation highlighted 'fun' and enjoyment, emotion and sharing lived experiences as essential to making involvement a meaningful and worthwhile activity for public advisers, and while this repeats findings from other evaluations, these elements are not present in the standard list of principles [29,31,32].…”
Section: Discussionsupporting
confidence: 76%
“…Through Improbable, students did not merely enter a ‘theory learning’ process, but they also experienced an effectual process: creating art without pre-determined goals, in an uncertain and ambiguous environment (Sarasvathy, 2008). Importantly, such a detour with the art world and rules avoided the reproduction of simplifying dichotomies (Beyes and Michels, 2012; Lorino et al, 2011) such as art versus business, creative versus non-creative individuals, experts versus amateurs, explicit versus tacit knowledge, rationality versus emotions or mind versus body (Komporozos-Athanasiou and Fotaki, 2015; Komporozos-Athanasiou and Thompson, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown how government-convened spaces for 'participation' commonly exclude or reify patient experiences (Renedo et al, 2017), discounting them as 'unrepresentative' (Martin, 2008) or irrational (Komporozos-Athanasiou and Thompson, 2015;Renedo et al, 2017), serving ultimately to legitimate existing priorities and pre-decided agendas (KomporozosAthanasiou et al, 2016). Moreover, in a field rich with history of bottom-up participation such as health social movements (e.g.…”
Section: Accepted For Publication In Human Relationsmentioning
confidence: 99%